Treacher Collins Syndrome - A Case Report - Islam, Farzana; Afroza, Ainun; Rukunuzzaman, Md; Rahman, Atiar; Hassan, Shariful (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v32i1.6011 Bangladesh Journal of Child Health 2008; Vol.32(1): 33-36